Financial Literacy and Demographic Factors in Karachi City of Pakistan - Samra Suhail; Dr. Abdur Rahman Aleem; Masood; Dr. Imam Uddin; Muhammad AsadUllah (Reviews of Management Sciences, 2021)
Considering the vigorously dynamic fluctuations in the monetary condition, particularly in financial/budgetary markets, it is urged to improve speculators’ money managing knowledge. Financial proficiency involves making well aware and efficient financial choices. The present examination explores the socio-economic factors defining Pakistani investors’ financial literacy and effects of financial literacy on stock market investment decision. A (questionnaire) survey was developed based on 3 sections: The primary section included the measuring of demographic characteristics of respondents, the secondary was based on measuring financial literacy of respondents, whereas the last section was dedicated to measuring stock market investment decision of respondents.